Maintaining Brand Loyalty Through Integrated Marketing Communication (IMC): Insights from PT Dream Tours and Travel - Iswara R., Putri Debby; Purnamasari, Oktaviana (Transpublika Publisher, 2025)
The competitive Hajj and Umrah travel market struggles with brand loyalty due to intense competition, changing pilgrim numbers, and the importance of customer trust. Companies must use effective strategies to avoid losing market share. This research focuses on the implementation of Integrated Marketing Communication (IMC) by PT Dream Tours and Travel to retain customers. This research aims to analyze PT Dream Tours and Travel's Integrated Marketing Communication (IMC) implementation and brand loyalty. IMC was chosen as a concept approach to create consistent and effective marketing communication through various channels such as advertising, sales promotion, digital media, and public relations. IMC, as stated by Andrews & Shimp is a marketing approach that integrates various communication elements, such as advertising, sales promotion, direct marketing, public relations, and digital media, to create consistent messages and build long-term relationships with customers. This research uses a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, observation, and analysis of company documents. The main informants consisted of the management of PT Dream Tours and Travel and Umrah pilgrims. The results showed that the implementation of IMC by PT Dream Tours and Travel succeeded in increasing brand loyalty with integrated marketing methods and based on consumer needs. Consistent promotion through social media, banking partnerships, and special programs such as Hajj savings have proven effective in attracting new customers while maintaining relationships with existing customers.